2010
DOI: 10.5012/bkcs.2010.31.10.2939
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of a New High-Temperature pH Sensor for Use in PWR Nuclear Power Plants

Abstract: A new high-temperature pH sensor has been successfully developed by reforming the internal reference systems of the pH sensors based on oxygen-ion conducting ceramic membrane. The conventional internal reference system, a mixture of Ni and NiO, has been replaced with partially oxidized Ni powders, where Ni and NiO coexist on the surface of particles, in order to avoid the cumbersome mixing step of Ni and NiO particles. The partially oxidized Ni particles were made by oxidizing Ni under air atmosphere at 600 o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…An early study by Inda et al [54] showed that the YSZ probe followed an almost Nernstian response to potential as a function of pH and gave a stable pH reading within 30 s, as opposed to other probes, which can take significantly longer. At the same time, Jung and Yeon [55] designed a loop system using stainless steel coated in titanium and a YSZ probe to measure the pH of coolants in pressurized water reactors and were capable of accurately measuring pH at 280 • C. A comprehensive study by Truche et al [56] measured the pH in-situ of NaCl hydrothermal solutions at temperatures up to 280 • C and 150 bar. The pH probe was an oxygen-ion conducting ceramic sensor coupled to an Ag/AgCl reference electrode.…”
Section: Industrial Applications Of In-line Ph Measurement Under Chal...mentioning
confidence: 99%
“…An early study by Inda et al [54] showed that the YSZ probe followed an almost Nernstian response to potential as a function of pH and gave a stable pH reading within 30 s, as opposed to other probes, which can take significantly longer. At the same time, Jung and Yeon [55] designed a loop system using stainless steel coated in titanium and a YSZ probe to measure the pH of coolants in pressurized water reactors and were capable of accurately measuring pH at 280 • C. A comprehensive study by Truche et al [56] measured the pH in-situ of NaCl hydrothermal solutions at temperatures up to 280 • C and 150 bar. The pH probe was an oxygen-ion conducting ceramic sensor coupled to an Ag/AgCl reference electrode.…”
Section: Industrial Applications Of In-line Ph Measurement Under Chal...mentioning
confidence: 99%